Lon protease inactivation in Drosophila causes unfolded protein stress and inhibition of mitochondrial translation. Issue 1 (December 2018) - Pareek, Gautam; Thomas, Ruth; Vincow, Evelyn; Morris, David; Pallanck, Leo
Abstract Mitochondrial dysfunction is a frequent participant in common diseases and a principal suspect in aging. To combat mitochondrial dysfunction, eukaryotes have evolved a large repertoire of quality control mechanisms. One such mechanism involves the selective degradation of damaged or misfolded mitochondrial proteins by mitochondrial resident proteases, including proteases of theA TPaseA ssociated with diverse cellularA ctivities (AAA+ ) family. The importance of the AAA+ family of mitochondrial proteases is exemplified by the fact that mutations that impair their functions cause a variety of human diseases, yet our knowledge of the cellular responses to their inactivation is limited. To address this matter, we created and characterized flies with complete or partial inactivation of theDrosophila matrix-localized AAA+ protease Lon. We found that aLon null allele confers early larval lethality and that severely reducing Lon expression using RNAi results in shortened lifespan, locomotor impairment, and respiratory defects specific to respiratory chain complexes that contain mitochondrially encoded subunits. The respiratory chain defects ofLon knockdown (Lon KD ) flies appeared to result from severely reduced translation of mitochondrially encoded genes. This translational defect was not a consequence of reduced mitochondrial transcription, as evidenced by the fact that mitochondrial transcripts were elevated in abundance inLon KD flies. Rather, the translational defect ofLon KD flies appeared to be derived from sequestration of mitochondrially encoded transcripts in highly dense ribonucleoparticles. The translational defect ofLon KD flies was also accompanied by a substantial increase in unfolded mitochondrial proteins. Together, our findings suggest that the accumulation of unfolded mitochondrial proteins triggers a stress response that culminates in the inhibition of mitochondrial translation. Our work provides a foundation to explore the underlying molecular mechanisms.